PROFIL INTERLEUKIN PRO INFLAMASI PADA PASIEN TB - Edwin Anto Pakpahan; Hendrika Andriana Silitonga (Universitas Methodist Indonesia, 2018)
Tuberculosis is an infectious disease caused by germs from the Mycobacterium group, Mycobacterium tuberculosis. There are several species of Mycobacterium, including: M. tuberculosis, M. africanum, M. bovis, M. leprae etc, which is also known as Acid Resistant Bacteria (BTA). The group of Mycobacterium bacteria besides Mycobacterium tuberculosis which can cause disruption in the airways is known as MOTT (Mycobacterium Other Than Tuberculosis) that sometimes can interfere the enforcement of TB diagnosis and treatment. For this reason, bacteriological examination capable of identifying Mycobacterium tuberculosis is an ideal diagnostic tool for TB and the strong predictor of early treatment success. However, it is not uncommon for patients who have carried out of TB program treatment, because they are not be able to remove sputum at the end of the evaluation, so that bacteriological healing is difficult to convey to these patients. Therefore another way to find out that they have healed or not is by doing a pro inflammatory interleukin examination.